Caring for young adult men with inflammatory bowel disease: Clinician and patient perspectives - Amy K. Bugwadia; Sydney Reed; Adam Finkelstein; Peter Park; Colin Quinn; Sneha Dave; Nikhil Jayswal; Grady Stewart; David Kohler; Noel Jacobs; Grant E. Barber (Health Care Transitions)
Inflammatory bowel disease (IBD) presents unique challenges for young adult men that extend beyond physical symptoms, encompassing psychosocial dimensions affecting all aspects of life. This article draws insights from a roundtable discussion facilitated by the Crohn's and Colitis Young Adults Network (CCYAN), focusing on the experiences of young men living with IBD. It sheds light on the intersections of IBD and men's sexual and reproductive health, fertility, and mental well-being while identifying gaps in care. The article offers recommendations for clinicians and emphasizes the role of care partners and social support, underlining the need for dedicated support structures to improve the lives of men living with IBD.